Jacks of all trades : the role of exhibition officers in regional museums : four case studies from the lower North Island, New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Museum Studies at Massey University - McAdam, Stephen Graeme (Massey University, 1996)
The aim of this thesis is to explore the roles of Exhibition Officers who work in regional museums in New Zealand. Research comprised interviews with the Exhibition Officers, Directors and Curators (or equivalent) of four institutions, and an examination of institutional documents, including job descriptions, salary scales and annual reports. The roles of Exhibition Officers include the design, fabrication and installation of exhibitions; the design of publicity material and some functions traditionally regarded as "curatorial". The variety of roles is partly due to institutional requirements of these positions and partly because of the wide range of skills which Exhibition Officers bring from previous training and experience. The extent of the curatorial functions performed by Exhibition Officers depends on the boundaries of the Curators roles in each institution. Two of the participant Exhibition Officers had a major role in the curation of exhibitions. The flexibility of roles in some institutions makes it imperative that there is a mutual understanding of each other's roles by Exhibition Officer and Curator. A discussion of the status of Exhibition Officers in their own institutions and among the wider body of museums was important to the discussion of their roles. While Directors spoke of the high esteem in which they held their Exhibition Officers, in most instances this was not matched by awarding them with a salary that equated with other high status positions such as the institutions' Curators. Where status may affect the performance of the Exhibition Officer is in resource allocation. It is clear that in comparison to curatorial functions, the exhibitions function in some of the case study museums has a low priority in the allocation of staff resources. It is likely that the lack of recognised qualifications held by Exhibition Officers constrains their status among the wider body of museum workers. This is hindered by the fact that there is currently very little appropriate training for Exhibition Officers. The informality of communication and exhibition planning documented in this study is at odds with the formalised and prescriptive approaches to be found in museological texts. There is a need for the development of literature on museum practice derived from ethnographic studies in New Zealand museums and museums of similar size and function in other countries. This will provide practitioners and students with a more accurate representation of issues and practices in museums than some museological texts drawn from the larger institutions overseas. A discussion of exhibition planning in the participant museums showed that the inter-relationship between museums and the public needs to be enhanced by making exhibitions more visitor-focused. This may be achieved by instituting formal evaluation of exhibitions and focus group research. It was apparent that there was little critical feedback from the public on museum exhibitions. This makes it difficult for Exhibition Officers to ascertain if exhibitions are meeting goals, or if exhibitions are being provided that the public wish to see. This thesis supports the contention that to understand the workings of museums, more research on the roles of museum staff and museum practice must be carried out.
Keywords: New Zealand; Museum techniques; Exhibitions